Representasi Perempuan Berdaya Pada Akun Instagram @Ciledugfemalecommunity - Permata, Sandy; Kencana, Woro Harkandi; Bahriyah, Euis Nurul (KOMUNIKOLOGI: Jurnal Ilmiah Ilmu Komunikasi, 2026)
The development of social media, especially visual-based platforms like Instagram, has changed the way women construct their identities, including through virtual women's communities. This study examines the representation of empowered women on the Instagram account @ciledugfemalecommunity, a community of women residing in the Ciledug area and its surroundings. The methodology used is a qualitative approach with content analysis methods to analyze the themes, visuals, and narratives in the account's bio, photos/videos, and captions. This study shows that empowered women are represented in three dominant main themes: women as drivers of local communities, women as subjects of "sisterhood" relationships, and women based on local Ciledug identity. At the visual level, this community is an image of women in the dynamics of togetherness, actively involved in activities, and represents self-confidence through spoken language and hashtags that emphasize learning and empowerment.